The role of political leaders in addressing political crises Iraqi social movements after 2003 as a model. - Razak, Faten Mohamed (The International and Political Journal, 2022)
After 2003, Iraq faced a group of forms of social movements distributed between (sit-ins, marches, civil disobedience, uprisings, most notably demonstrations) to be considered a kind of political participation that expresses popular dissatisfaction with the political process with all its internal and external interactions and the resulting political, economic and security crises that expressed the weakness and failure of the political leadership In managing the crisis because it followed a variety of methods that varied between the method of denial of the existence of the crisis or suppression and suppression, which made Iraq in repeated crises. The Iraqi demonstrations, especially October 2019, represented one of the images of those crises. Therefore, the study dealt with the relationship of the Iraqi political leadership with Iraqi demonstrations and its role in crisis management, as well as the types of demonstrations and their role in Achieving political, economic or security gains..